1998
DOI: 10.1136/ebmh.1.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for evaluating prevalence studies

Abstract: As stated in the first issue of Evidence-Based Mental Health, we are planning to widen the scope of the journal to include studies answering additional types of clinical questions. One of our first priorities has been to develop criteria for studies providing information about the prevalence of psychiatric disorders, both in the population and in specific clinical settings. We invited the following editorial from Dr Michael Boyle to highlight the key methodological issues involved in the critical appraisal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
236
1
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(261 citation statements)
references
References 3 publications
0
236
1
12
Order By: Relevance
“…Two independent reviewers assessed the risk of bias related to methodological aspects of included studies using the Cochrane Collaboration tool for randomised controlled trials (RCT) [17], and published guidelines for crosssectional prevalence studies [18]. Discrepancies were resolved by discussion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two independent reviewers assessed the risk of bias related to methodological aspects of included studies using the Cochrane Collaboration tool for randomised controlled trials (RCT) [17], and published guidelines for crosssectional prevalence studies [18]. Discrepancies were resolved by discussion.…”
Section: Methodsmentioning
confidence: 99%
“…Criteria were developed to determine whether each feature had been adequately addressed, not adequately addressed, or if there was insufficient information to decide. An adequate response rate was defined by Boyle as >80% [18]. There were no studies in this review with such a high response rate so we reported those with a response rate of >60% and >70%.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies 13,14,15,16,17,18,19 in recent years have attempted to understand more about low back pain and how to manage it. However, precise estimates of low back pain prevalence are necessary to elucidate the developmental perspective of low back pain in different countries 20 . Prevalence studies are widely used in epidemiology due their economic feasibility and easiness, with relatively short duration, providing indicators of the community's health situation, based on evaluation of the individual health status in each member of the group and producing global health indicators for the target group 21 .…”
Section: Introductionmentioning
confidence: 99%